Blocajele actorului. Tehnici și metode în dezvoltarea creativității scenice - Ardelean, Ioan (Theatrical Research, 2025)
The Actor’s Blocks. Techniques and Methods in the Development of Scenic Creativity The book The Actor’s Blocks. Techniques and Methods in the Development of Scenic Creativity by Elena Purea traces, observes, and investigates one of the major problems acting students encounter: creative blocks. The author explores the causes of these emotional, psychological, or physical blockages and proposes ways to overcome them through techniques inspired by Sanford Meisner and Michael Chekhov. The practical part includes exercises based on confidence, freedom of expression, the release of muscular tension or body rigidity, and artistic authenticity. The author emphasizes the importance of a safe environment (nest) and a pedagogy that harmoniously blends elements of psychological theory with theatrical practice. The book is a valuable resource for actors, educators, and directors and is designed as a guide to help actors overcome their blocks and cultivate their creative potential.